N-doped M/CoO (M=Ni, Co, and Mn) hybrid grown on nickel foam as efficient electrocatalyst for the chemical-assisted water electrolysis. (29th January 2022) - Wang, Tuo; Cao, Yifei; Wu, Huimin; Feng, Chuanqi; Ding, Yu; Mei, He
Abstract: In this work, N-Ni1 Co3 Mn0.4 O/NF is synthesized as multifunctional electrocatalyst for hydrogen evolution (HER), urea oxidation reaction (UOR) and hydrazine oxidation reaction (HzOR). The optimal Ni/Co (molar ratio) and the amount of doping Mn are investigated, the sample with Ni/Co = 1:3 and the addition of 0.4 mmol Mn exhibits the best catalytic activity with the largest specific surface area. Then the two-electrode electrolyzers composed of N-Ni1 Co3 Mn0.4 O/NF are constructed, and the results from experiments show that the voltage required for overall hydrazine splitting (OHzS) at 100 mA cm −2 is 0.272 V, 1.614 V lower than that of overall water splitting (OWS, 1.886 V), while the overall urea splitting (OUS) needs 1.669 V, 0.187 V lower than that of OWS, revealing the outstanding thermodynamic and kinetic advantages of OUS and OHzS. The superior performance may be attributed to the heterostructure between metal and metal oxide and N-doping, which can promote electron transfer and optimizes the decomposition of urea and hydrazine hydrate and hydrogen production, and the research on mechanism will be carried out in the future. Highlights: A general method is reported for synthesizing microsphere. The material has demonstrated excellent structural advantages for electrocatalysis. The electrode has shown excellent activities for HER, UOR, and HzOR. The OUS and OHzS have extremely large kinetic advantage compared with OWS.